THE BENEFITS OF USING ENTERPRISE CONTENT MANAGEMENT (ECM) SYSTEM TO MANAGE CONTENT IN HIGHER EDUCATION INSTITUTIONS: A SCOPING REVIEW - Mkhize, Lindokuhle; Salamntu , Lumka T. P. (Journal of Islamic, Social, Economics and Development, 2024)
Higher Education Institutions (HEIs) face a substantial challenge in effectively managing content and this is primarily due to the rapidly growing volume of digital content. In an attempt to manage the increased content, the HEIs have adopted an Enterprise Content Management (ECM) system. ECM is a system used to capture, manage, store, preserve, deliver content. The ECM vendors promise a number of benefits associated with its use. However, the benefits are not understood in HEIs. Thus, this study aims to explore the benefits of using ECM in HEIs. Given the paucity of research on the benefits of using ECM systems in HEIs, this scoping review aims to provide researchers with a comprehensive understanding of these benefits. A scoping review was conducted guided by the Preferred Reporting Items for Systematic Review and Meta-Analysis for Scoping Reviews (PRISMA-ScR). An eligibility criterion was established and only studies that focused on ECM in HEIs were included. A search string encompassing of five databases resulted in thirteen eligible studies, and a backward search of the references resulted in an additional of fourteen publications. Of the 27 studies, the majority followed a qualitative research approach (81.5%), most studies were conducted in the year 2020 (37.0%) and (74.1%) of the studies used an interpretivism research philosophy. This review reveals that cost reduction was the most dominant benefit of managing content in HEIs while data consistency and retaining of organisational memory were the least significant benefits. This review provides a comprehensive understanding of the benefits of the use of ECM system in HEIs. Future studies should focus on how to ensure that the benefits are communicated in HEIs so as to enhance the effectiveness and efficiency of their ECM systems.